Camellia piloflora (Theaceae), a new yellow camellia from Guangxi, South China - Zhang, Qiong; Wu, Fang-Yuan; Huang, Yao-Heng; Ma, Jin-Lin; Yang, Shi-Xiong (Phytotaxa, 2022)
Camellia piloflora, a new yellow camellia from southwestern Guangxi, China, is described and illustrated. Morphologically, it is closest related to C. debaoensis, but differs by its puberulent sepals, pubescent filaments, and tomentose ovary and style.